1997
DOI: 10.1128/mcb.17.3.1595
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Signalling by the Insulin-Like Growth Factor I Receptor, Phosphatidylinositol 3-Kinase, and Akt

Abstract: We have found that insulin-like growth factor I (IGF-I) can protect fibroblasts from apoptosis induced by UV-B light. Antiapoptotic signalling by the IGF-I receptor depended on receptor kinase activity, as cells overexpressing kinase-defective receptor mutants could not be protected by IGF-I. Overexpression of a kinasedefective receptor which contained a mutation in the ATP binding loop functioned as a dominant negative and sensitized cells to apoptosis. The antiapoptotic capacity of the IGF-I receptor was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
757
5
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 984 publications
(809 citation statements)
references
References 67 publications
40
757
5
7
Order By: Relevance
“…Similarly to the observation made for IGF-IR signalling in Rat-1 cells by Kulik et al (1997), the MAPK inhibitor PD098059 had no e ect on survival signalling of wt-TrkA against MycER TM or U.V.-induced apoptosis in our cell-system (data not shown). These data are consistent with the fact that NGF induced survival in primary sympathetic neurones is not blocked by PD098059 (Creedon et al, 1996;Virdee and Tolkovsky, 1996) suggesting that ± at least in the cell systems mentioned above ± MAPK does not add to the survival signals of IGF-IR or TrkA.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly to the observation made for IGF-IR signalling in Rat-1 cells by Kulik et al (1997), the MAPK inhibitor PD098059 had no e ect on survival signalling of wt-TrkA against MycER TM or U.V.-induced apoptosis in our cell-system (data not shown). These data are consistent with the fact that NGF induced survival in primary sympathetic neurones is not blocked by PD098059 (Creedon et al, 1996;Virdee and Tolkovsky, 1996) suggesting that ± at least in the cell systems mentioned above ± MAPK does not add to the survival signals of IGF-IR or TrkA.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, overexpression of constitutively active forms of the PI3-kinase target Akt/PKB has been shown to be su cient to block apoptosis in a number of cell types (Dudek et al, 1997;Kulik et al, 1997;Kau mannZeh et al, 1997;Khwaja et al, 1997). NGFstimulated TrkA activates PI3-kinase in both PC12 cells and in Âźbroblasts expressing TrkA (Carter and Downes, 1992;Ra oni and Bradshaw, 1992;Solto et al, 1992;Ohmichi et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 PI3-K is thought to be one of the key molecules involved in the signaling pathways of activated receptor tyrosine kinases and in the regulation of cell growth, motility, and morphogenesis. [33][34][35] Shayesteh et al 36 demonstrated that the copy number of PIK3CA, the gene encoding the P110a catalytic subunit of PI3-K, was increased in approximately 80% of primary ovarian cancers and several ovarian cancer cell lines. It has also been demonstrated that another PI3-K inhibitor, LY294002, significantly inhibited tumor growth and ascites formation by ovarian carcinoma in vivo and markedly inhibited cancer cell proliferation in vitro, suggesting an important role of PI3-K in the growth of ovarian carcinoma.…”
Section: Actinin-4 and Ovarian Cancer S Yamamoto Et Almentioning
confidence: 99%
“…6, S6 and S7), which is surprising because loss of PTEN is often associated with suppression of apoptosis and enhanced cell survival (Brunet et al., 1999; Kulik, Klippel, & Weber, 1997). These responses are elicited in immortalized cell lines or cell lines following irradiation‐induced DNA damage, which are not normal, WT cells or conditions.…”
Section: Discussionmentioning
confidence: 99%